FINANCIAL TECHNOLOGY (FINTECH): ITS ROLE IN CHANGING PEOPLE'S MONEY MANAGEMENT BEHAVIOR - Subur karyatun (Jurnal Ekonomi, 2023)
The Fintech phenomenon has significantly changed the way people manage and interact with their personal finances. The adoption of financial technology has influenced consumer behavior, risk management, access to financial services, and the financial stability of society as a whole. This research aims to investigate the impact and role of financial technology (Fintech) in changing people's money management patterns. This research uses a qualitative approach with descriptive methods. The research results show that the development of Financial Technology (Fintech) in Indonesia has a significant impact on people's financial management behavior and business transformation. The growth of Fintech, such as digital payments, online loans and digital investments, provides wider access to individuals and businesses. Digital investment apps increase financial literacy, while online loans provide opportunities for small entrepreneurs. Fintech is also influencing traditional businesses by integrating technology to increase efficiency. The use of Market Comparison in fintech provides better access to various investment options. However, regulatory and consumer protection challenges still need to be addressed. Overall, this research shows that Fintech is shaping the modern financial landscape and encouraging society's adaptation to technological changes in Indonesia.